Health risk assessment of heavy metals in Malay herbal medicine (MHM) consumed by pregnant and postpartum mothers - Bustami, Normina Ahmad; Tan, Chung Keat; Lee, Yu Zhao; Zaman, Rahela; Ho, Yu Bin; Aris, Ahmad Zaharin; Sadat, Marjan; Tan, Eugenie Sin Sing (Springer, 2024)
Background Malay herbal medicine (MHM) is a popular medication and supplementation among Malaysian mothers during pregnancy and postpartum. It is expected to improve the baby’s health, increase breastmilk production, promote slimming and uterine involution, and improve the mother’s general health. Recent increases in reports of heavy metal contamination have raised safety concerns. Objective This pilot exploratory study employed a comparative cross-sectional design to investigate the types of MHM ingested during pregnancy and postpartum, their possible heavy metal contamination and associated health risks. Method This study involved 167 healthy postpartum Malay women. Findings MHM consumption was signifcantly associated with the mother’s number of pregnancies and children (p<0.05) as well as her pre-pregnancy weight (p<0.05). Mothers who consume MHM were twice as likely (95% CI 1.077–3.963) to experience threatened abortion. Heavy metals were detected in the three most widely consumed MHM samples. The mean concentration of heavy metals in these samples were 47.44 ±67.74 μg/kg for As, 25.34±2.48 μg/kg for Cd, 3685.87±5683.36 μg/kg for Cr and 194.33±195.19 μg/kg for Pb. The calculated non-carcinogenic hazard health risks (HQ) and health index (HI) were less than one, suggesting no adverse health impacts under the exposure conditions studied. Conclusion While the HQ and HI values indicate no immediate health risks, the potential transfer from mother to foetus during pregnancy and from mother to infant during breastfeeding warrants further investigation. Additional studies are essential to confrm our fndings and monitor the health of mothers and infants.